Political Atmosphere In Rural Economic Develovment In Citengah Village, Sumedang Regency - Mila Meliana; Mulyaningsih (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract Rural economic development is an integral part of national development that is greatly influenced by local political dynamics. This study analyzes the relationship between political atmosphere and economic development in Citengah Village, Sumedang Regency. Using a qualitative approach, this study reveals that local political stability, development policies, and the role of political actors greatly determine the effectiveness of the implementation of village economic programs. The results of the study indicate that politicization of policies, uneven allocation of village funds, and lack of transparency in the management of Village-Owned Enterprises (BUMDes) are the main challenges in economic development in Citengah Village. However, this village also has great opportunities in developing an economy based on local resources, such as the agricultural and agro-tourism sectors. Community empowerment, strengthening the role of the village government, and optimizing BUMDes as an economic driver are the main strategies in realizing inclusive and sustainable development. This study recommends increasing transparency in village governance and synergy between the government, community, and private sector to support rural economic growth.